Guiding Mobile Robot by Applying Fuzzy Approach on Sonar Sensors - Abid Al- Sahib, Nabeel K.; Jasim, Ahmed Rahman (Al-Khwarizmi Engineering Journal, 2010)
This study describes how fuzzy logic control FLC can be applied to sonars of mobile robot. The fuzzy logic approach has effects on the navigation of mobile robots in a partially known environment that are used in different industrial and society applications. The fuzzy logic provides a mechanism for combining sensor data from all sonar sensors which present different information. The FLC approach is achieved by means of Fuzzy Decision Making method type of fuzzy logic controller. The proposed controller is responsible for the obstacle avoidance of the mobile robot while traveling through a map from a home point to a goal point. The FLC is built as a subprogram based on the intelligent architecture (IA). The software program  uses the Advanced Robotics Interface for Applications (ARIA), it is programmed with C++ package ( Visual C++.Net ), and Networking software is used for setup Wireless TCP/IP Ethernet-to-Serial connection between robot and PC. The results show that the developed mobile robot travels successfully from one location to another and reaches its goal after avoiding all obstacles that are located in its way. The platform mobile robot is a Pioneer 3 DX that is equipped with Sonar sensors.